2022
DOI: 10.1163/27730840-54010003
|View full text |Cite
|
Sign up to set email alerts
|

Cost and Affordability of School Uniform and Child Poverty

Abstract: Although there are no attendance or registration fees in the UK for publicly funded school education there are hidden costs in attending compulsory education. This article investigates one of the hidden costs: school uniform. We investigate the affordability of school uniform in Scotland, looking at what is required in school uniform policy (class uniform and Physical Education kit), the costs of uniform and to what extent the national minimum clothing grant makes uniform affordable for households on low incom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 19 publications
0
0
0
Order By: Relevance
“…School uniforms are common in many primary and secondary school settings globally. 24 While some researchers have explored their relationship with other outcomes 25 , 26 , 27 , 28 , 29 , 30 (e.g., academic achievement 27 , 31 and social behavior 28 ), finding no or inconsistent correlations, studies examining associations with gender inequalities in physical activity are limited. Previous researchers who explored UK adolescent girls’ experiences of physical activity at school through the lens of comfort theory 32 found that female participants perceived their PE uniform as a barrier to physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…School uniforms are common in many primary and secondary school settings globally. 24 While some researchers have explored their relationship with other outcomes 25 , 26 , 27 , 28 , 29 , 30 (e.g., academic achievement 27 , 31 and social behavior 28 ), finding no or inconsistent correlations, studies examining associations with gender inequalities in physical activity are limited. Previous researchers who explored UK adolescent girls’ experiences of physical activity at school through the lens of comfort theory 32 found that female participants perceived their PE uniform as a barrier to physical activity.…”
Section: Introductionmentioning
confidence: 99%